2004
DOI: 10.1002/app.21214
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrasonic oscillations on processing behavior and mechanical properties of metallocene‐catalyzed linear low‐density polyethylene/low‐density polyethylene blends

Abstract: ABSTRACT:The influences of ultrasonic oscillations on rheological behavior and mechanical properties of metallocene-catalyzed linear low-density polyethylene (mLLDPE)/ low-density polyethylene (LDPE) blends were investigated. The experimental results showed that the presence of ultrasonic oscillations can increase the extrusion productivity of mLLDPE/LDPE blends and decrease their die pressure and melt viscosity during extrusion. Incorporation of LDPE increases the critical shear rate for sharkskin formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…5 Many studies on devulcanization were reviewed in the book chapter. 6 Later, ultrasonically aided processing was used to prepare various polymer blends, including high-density polyethylene (HDPE)/polystyrene (PS), 7,8 polypropylene (PP)/PS, 9 PP/ethylene propylene diene methylene (EPDM) rubber, [10][11][12][13][14][15][16] PP/natural rubber (NR), 10,11,17 HDPE/NR, 10,11 HDPE/ EPDM, 10,11 HDPE/styrene butadiene rubber (SBR), 10,11 NR/SBR, 10,11 PP/ultrahighmolecular weight polyethylene, 18 linear low-density polyethylene (LLDPE)/lowdensity polyethylene, 19,20 HDPE/polyamide 6 (PA6), 21 PS/EPDM, 22,23 PP/PA6, 24 poly(lactic acid)/poly(butylene adipate-co-terephthalate), 25 ethylene-a-olefin copolymers (POE)/PS, 26 PA6/POE/POE grafted with maleic anhydride (POE-g-MAH), 27 LLDPE/POE, 28 polyethylene terephthalate (PET)/LCP, 29 polyethylene naphthalate (PEN)/liquid crystalline polymers (LCP), 30 PET/PEN, 31 blends of two different LCPs. 32 Most articles reported the in situ copolymerization of polymers by the ultrasonic treatment, as patented by Isayev and Hong.…”
Section: Introductionmentioning
confidence: 99%
“…5 Many studies on devulcanization were reviewed in the book chapter. 6 Later, ultrasonically aided processing was used to prepare various polymer blends, including high-density polyethylene (HDPE)/polystyrene (PS), 7,8 polypropylene (PP)/PS, 9 PP/ethylene propylene diene methylene (EPDM) rubber, [10][11][12][13][14][15][16] PP/natural rubber (NR), 10,11,17 HDPE/NR, 10,11 HDPE/ EPDM, 10,11 HDPE/styrene butadiene rubber (SBR), 10,11 NR/SBR, 10,11 PP/ultrahighmolecular weight polyethylene, 18 linear low-density polyethylene (LLDPE)/lowdensity polyethylene, 19,20 HDPE/polyamide 6 (PA6), 21 PS/EPDM, 22,23 PP/PA6, 24 poly(lactic acid)/poly(butylene adipate-co-terephthalate), 25 ethylene-a-olefin copolymers (POE)/PS, 26 PA6/POE/POE grafted with maleic anhydride (POE-g-MAH), 27 LLDPE/POE, 28 polyethylene terephthalate (PET)/LCP, 29 polyethylene naphthalate (PEN)/liquid crystalline polymers (LCP), 30 PET/PEN, 31 blends of two different LCPs. 32 Most articles reported the in situ copolymerization of polymers by the ultrasonic treatment, as patented by Isayev and Hong.…”
Section: Introductionmentioning
confidence: 99%
“…Also, suppression of the sharkskin phenomenon on LLDPE extrudates was achieved27 along with breakup of the dispersed phase of polyolefin elastomer (POE) in metallocene catalyzed LLDPE/POE blend 28. Ultrasonically aided extrusion also led to an improvement of the elongation at break of LDPE/LLDPE blends 29. An addition of the diatomite/polyethylene glycol mixture to LLDPE led to an increase of the critical shear rate for the onset of sharkskin fracture and, in the presence of ultrasonic treatment, an improvement of the processibility of the LLDPE mixture was reported 30…”
Section: Introductionmentioning
confidence: 95%
“…A few studies on the effect of ultrasound on pure LLDPE were reported 27–30. In particular, they showed that an ultrasonically aided single screw extrusion improved processing of LLDPE by reducing the die pressure and melt viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…In our laboratory, ultrasonic oscillations are applied to polymer melt extrusion processing so as to improve the processing properties of the polymers and the compatibility of immiscible polymer blends 9–12. We found that ultrasonic oscillations can decrease die pressure and melt apparent viscosity, but increase flow rate and critical shear rate of mLLDPE and its blends with LDPE 13–14. Ultrasonic oscillations as well as the addition of LDPE help to improve the processing properties of mLLDPE.…”
Section: Introductionmentioning
confidence: 96%